Analisis Yuridis Kelalaian dan Pertanggungjawaban Pidana Kebakaran Hutan di Gunung Bromo Akibat Flare Prewedding: Studi Putusan No. 305/Pid.B/Lh/2023/Pn Krs - Farida Nurun Nazah; Karindra Alvian Nugraha; Syifa Ramadani Ramadani; Muhamad Noval Faris Pratama; Nayla Azzahra Khaerunnisa; Talitha Maheswari Ning Atmojo (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes the element of negligence (culpa) and criminal liability in a forest fire case at Bromo Tengger Semeru National Park caused by a prewedding flare, based on Decision No. 305/Pid.B/LH/2023/PN Krs. Using normative legal methods with statutory and case approaches, the findings prove culpa through flare use in a dry savanna without risk mitigation, with a clear causal link. Criminal liability rests on fulfilled offense elements, culpa lata, culpability and no grounds for excuse. This decision affirms criminal sanctions for negligence causing ecological damage. It is recommended that judges explicitly distinguish negligence qualifications in their considerations to strengthen legal certainty.